Predisposing conditions for condylar sag after intraoral vertical ramus osteotomy - Satoshi Rokutanda (Nature Portfolio, 2021)
Abstract Intraoral vertical ramus osteotomy (IVRO) is used to treat mandibular prognathism and temporomandibular disorders. However, the improvement of temporomandibular disorders after IVRO is considered to be due to the anterior and downward movement of the mandibular condyle, which may lead to condylar sag, and in the worst case, condylar luxation. In this retrospective cohort study, we examined factors potentially associated with condylar sag. Univariate analysis indicated that condylar sag was significantly associated with the following factors: magnitude of setback (P = 0.001), less than 3 mm setback (P < 0.001), presence of temporomandibular joint (TMJ) symptoms (P = 0.002), Wilkes classification (P = 0.039), occlusal cant correction ≥ 2 mm (P = 0.018), and mandibular condyle deformation (P < 0.001). Setback magnitude (P = 0.032) and TMJ symptoms (P = 0.007) remained significant in the multivariate analysis. In the receiver operating characteristic curve, the setback magnitude cut-off value for condylar sag after IVRO was 3.25 mm. Thus, the incidence of condylar sag after IVRO is increased with a smaller setback magnitude (≤ 3.25 mm) and the presence of TMJ symptoms. These factors should be evaluated by surgeons during treatment planning for IVRO to estimate condylar sag, and it may be possible to predict the risk of condylar luxation.